TINGKAT KEMANDIRIAN KEUANGAN RUMAH SAKIT UMUM PUSAT BADAN LAYANAN UMUM MILIK KEMENTERIAN KESEHATAN REPUBLIK INDONESIA - Indah Kusuma Astuti; Swarmilah Hariani (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
The purpose of this study is to determine the effect of financial performance as measured by indicators of current ratio, fixed asset turnover, return on asset and service performance as measured by indicators of bed occupancy ratio, turn over interval, and length of stay on the level of hospital financial independence. Object this research is a public hospital owned by the Ministry of Health of the Republic of Indonesia which has become the Public Service Agency (BLU). This study uses secondary data in 2016-2018.The results of this study indicate that financial performance (current ratio, fixed asset turnover, return on asset) and service performance (bed occupancy ratio, turn over interval, length of stay) together the same have a positive influence and significantly to the independence of the financial hospital measured by the indicator cost recovery rate. Partially, current ratio has a negative effect significant, fixed asset turnover have a positive effect not significant, return on assets have a positive effect of significant, bed occupancy ratio has a positive effect not significant, turn over interval have a positive effect not significant, and the length of stay have a negative effect not significantly to the independence of the financial hospital measured by the indicator cost recovery rate.